Tønsbergs sjøfart gjennom 100 år - Eriksen, Erling (Vestfoldminne, 1961)
Keywords: Sørishavet; Vestfold; historie; hvalfangstindustri; hvalkokerier; pelagisk; skipsbyggerier

Thermal and metabolic responses of men in the Antarctic to a standard cold stress - Milan, Frederick A; Elsner, Robert W; Rodahl, Kaare (Journal of Applied Physiology, 1961)
Thermal and metabolic responses of eight male subjects exposed nude for 2 hr to a standard cold stress (17 α 1.0 C air temperature) were examined in the austral fall, winter, and spring at Little America in the Antarctic. Mean body, average skin and foot temperatures increased significantly after 3 months. Neither rectal nor finger temperatures were changed over the year. Although basal metabolic rates were unchanged, there was a significant decrease in the metabolic responses to the standard cold stress after 3 months in the Antarctic. It is suggested that these changes represent physiological adaptations to chronic cold. Submitted on November 14, 1960
Keywords: Antarktis; fysiologi; kuldeeksponering; kuldetoleranse; medisin

To slags minkehval i Antarktis = Two kinds of minke whale in the Antarctic - Williamson, Gordon R (Norsk hvalfangst-tidende, 1961)
Keywords: Sørishavet; hvaler; marin zoologi; zoologi